Pengaruh Kualitas Produk, Beauty Vlogger, dan Citra Merek terhadap Keputusan Pembelian Produk Skincare Skintific di Kota Batam - Alya Afifah Puteri; Nora Pitri Nainggolan (ManBiz: Journal of Management and Business, 2026)
The purpose of this study is to examine how product quality, beauty vloggers, and brand image affect purchasing decisions for Skintific skincare products in Batam City, while quality and brand image are important factors influencing customers' decisions to buy the products. This study uses a quantitative methodology and descriptive analysis. This study employs multiple linear regression to analyze data collected through questionnaires distributed to 100 participants.The results of the multiple linear regression analysis showed that beauty vloggers influence purchasing decisions by 10.8%, product quality by 18.8%, and brand image by 35.3%. These three variables together can account for 76.2% of the variation in purchasing decisions, according to the coefficient of determination( R2). The t-test results indicate that beauty vloggers do not have a significant effect on the decision to purchase something, but product quality and brand image have a significant effect on the decision to purchase something. These findings help businesses create sustainable and effective skincare marketing strategies.